Anti-Tumor Necrosis Factor-α Therapy in the Management of Psoriasis and B-Chronic Lymphocytic Leukemia - Anna Balato; Serena Lembo; Teresa Cirillo; Matteo Megna; Annunziata Raimondo; Luisa Di Costanzo (Karger Publishers, 2011)
Psoriasis is a chronic immunologically-based inflammatory skin disease. B-chronic lymphocytic leukemia (B-CLL) is a form of leukemia characterized by the slow and progressive accumulation of monoclonal CD5+ B lymphocytes in peripheral blood, bone marrow, lymph nodes and other organs. A T-helper 1 cytokine-mediated pathway is involved in these disorders in which tumor necrosis factor-α (TNF-α) plays a central role. TNF-α is involved in physiological phenomena, such as host defense, inflammation and cell differentiation, and in many pathological conditions, such as fever and some malignant neoplasms. TNF-α involvement in psoriasis has been well validated by the clinical success of anti-TNF-α therapy. TNF-α has been well studied in the pathogenesis of B-CLL, suggesting it as a target in B-CLL therapy. We present the case of a patient suffering from plaque psoriasis and B-CLL. Since TNF-α is reported as a common link between psoriasis and B-CLL, the patient was treated with etanercept followed by infliximab, two anti-TNF-α drugs. During 3 years of therapy, the patient did not show significant modifications of lymphocyte levels, indicating no progression of B-CLL. We report this case to highlight the possibility to administer anti-TNF-α treatment in psoriatic patients affected by concomitant B-CLL.